Assessing and optimizing the potential for climate change mitigation and carbon sequestration in urban residential green spaces: energizing sustainable cities - Liu, Hancheng; Zhang, Jialong; Wang, Zijun (Frontiers in Environmental Science, 2025)
IntroductionUrban green spaces play a crucial role in mitigating climate change by sequestering atmospheric carbon dioxide. This study aimed to evaluate the carbon sequestration potential of common plant species in urban residential areas and provide recommendations for optimizing green space design and management.MethodsThe research was conducted in four residential areas of Nanjing, China, where key growth parameters of 20 plant species, including evergreen trees, deciduous trees, evergreen shrubs, and deciduous shrubs, were measured. The assimilation method was employed to calculate carbon sequestration per unit canopy area and for entire plants.ResultsThe results showed that the carbon sequestration capacities of different plant species and types exhibited significant differences, with p-values less than 0.05. In terms of daily carbon sequestration per unit canopy projection area, the ranking was as follows: evergreen trees > evergreen shrubs > deciduous trees > deciduous shrubs. For total plant carbon sequestration, the ranking was: evergreen trees > deciduous trees > evergreen shrubs > deciduous shrubs. Evergreen trees performed excellently in both carbon sequestration metrics, with the average daily carbon sequestration per unit canopy projection area and for the entire plant being 18.0024 g/(m2·d) and 462.28 g/d, respectively. The study also observed seasonal variations, with carbon sequestration rates being higher in autumn and summer compared to spring and winter. During the summer, the average daily carbon sequestration per unit canopy projection area and for the entire plant were 11.975 g/(m2·d) and 161.744 g/d, respectively, while in autumn, these values were 13.886 g/(m2·d) and 98.458 g/d. Seasonal variations were also observed, with autumn and summer exhibiting higher carbon sequestration rates compared to spring and winter. Additionally, CO2 concentrations were monitored across the four residential areas, providing insights into the spatial and temporal dynamics of carbon sequestration.DiscussionBased on the findings, optimization strategies were proposed, such as prioritizing the selection and integration of high-performing evergreen tree species in urban green space design and incorporating diverse plant types to enhance year-round carbon sequestration. This study contributes to the development of sustainable urban planning and landscape management practices, promoting the role of green spaces in mitigating climate change and enhancing urban resilience.